An adaptive dual-loop Lyapunov-based control scheme for a single-phase ups inverter - He, Jinsong (2022)
This letter proposes an adaptive Lyapunov-based control strategy for a single-phase uninterruptible power supply inverter with inherent dual control loops. The control law is derived via a proposed Lyapunov function which takes both dual-loop requirements and the global large-signal stability demand into account. Besides, in the proposed control scheme, the load disturbance is suppressed adaptively without any additional load-current sensors or observers. The load voltage is regulated with better steady-state and dynamic performance, as well as with great robustness against the parametric variations. Finally, experimental results verify the effectiveness of the proposed control scheme.